Predictors of Functional and Quality of Life Outcomes following Deep Brain Stimulation Surgery in Parkinson’s Disease Patients: Disease, Patient, and Surgical Factors - Hesham Abboud; Gencer Genc; Nicolas R. Thompson; Srivadee Oravivattanakul; Faisal Alsallom; Dennys Reyes; Kathy Wilson; Russell Cerejo; Xin Xin Yu; Darlene Floden; Anwar Ahmed; Michal Gostkowski; et al. (Parkinson's Disease)
Objective. The primary objective was to evaluate predictors of quality of life (QOL) and functional outcomes following deep brain stimulation (DBS) in Parkinson’s disease (PD) patients. The secondary objective was to identify predictors of global improvement. Methods. PD patients who underwent DBS at our Center from 2006 to 2011 were evaluated by chart review and email/phone survey. Postoperative UPDRS II and EQ-5D were analyzed using simple linear regression adjusting for preoperative score. For global outcomes, we utilized the Patient Global Impression of Change Scale (PGIS) and the Clinician Global Impression of Change Scale (CGIS). Results. There were 130 patients in the dataset. Preoperative and postoperative UPDRS II and EQ-5D were available for 45 patients, PGIS for 67 patients, and CGIS for 116 patients. Patients with falls/postural instability had 6-month functional scores and 1-year QOL scores that were significantly worse than patients without falls/postural instability. For every 1-point increase in preoperative UPDRS III and for every 1-unit increase in body mass index (BMI), the 6-month functional scores significantly worsened. Patients with tremors, without dyskinesia, and without gait-freezing were more likely to have “much” or “very much” improved CGIS. Conclusions. Presence of postural instability, high BMI, and worse baseline motor scores were the greatest predictors of poorer functional and QOL outcomes after DBS.